2014
DOI: 10.1007/s10877-014-9610-6
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of baseline lung impedance in chronic heart failure patients: use for monitoring pulmonary congestion and predicting admissions for decompensation

Abstract: The instantaneous lung impedance (ILI) is one of the methods to assess pulmonary congestion or edema (PCE) in chronic heart failure (CHF) patients. Due to usually existing PCE in CHF patients when evaluated, baseline lung impedance (BLI) is unknown. Therefore, the relation of ILI to BLI is unknown. Our aim was to evaluate methods to calculate and appraise BLI or its derivative as reflecting the clinical status of CHF patients. ILI and New York Heart Association (NYHA) class were assessed in 222 patients (67 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
2
15
0
1
Order By: Relevance
“…In the present study, we obtained a ΔLIR mean value of −30% at discharge in the ΔPC ≤ median subgroup, representing significant residual congestion, and mean ΔLIR = −20% in the ΔPC > median subgroup when ΔLIR = 0 corresponds to the normal baseline condition. Previously, we have shown that a ΔLIR value of −30% is compatible with mild to moderate alveolar oedema, while a value of −20% corresponds to mild–moderate interstitial congestion . This explains the absence of rales on lung auscultation at discharge in 52% of patients in the present study, at a time when lung impedance and the chest radiograph demonstrate interstitial congestion .…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…In the present study, we obtained a ΔLIR mean value of −30% at discharge in the ΔPC ≤ median subgroup, representing significant residual congestion, and mean ΔLIR = −20% in the ΔPC > median subgroup when ΔLIR = 0 corresponds to the normal baseline condition. Previously, we have shown that a ΔLIR value of −30% is compatible with mild to moderate alveolar oedema, while a value of −20% corresponds to mild–moderate interstitial congestion . This explains the absence of rales on lung auscultation at discharge in 52% of patients in the present study, at a time when lung impedance and the chest radiograph demonstrate interstitial congestion .…”
Section: Discussionsupporting
confidence: 71%
“…Unlike the existing impedance devices, the present device has the ability to differentiate a true signal from the lungs (positive signal) from the noise signal of surrounding chest wall, which is at least an order of magnitude larger. The sensitivity of this device to measure small accumulation of lung fluid has allowed the initiation of pre‐emptive LI‐guided treatment long before the appearance of the initial clinical signs of lung oedema and attendant deterioration . A method to determine individual normal or ‘dry’ baseline LI for each HF patient has been previously reported .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations